A novel approach for the synthesis of imidazo and triazolopyridines from dithioesters. (18th July 2016) - Ramesha, Ajjahalli B.; Sandhya, Nagarakere C.; Pavan Kumar, Chottanahalli S.; Hiremath, Mahanthawamy; Mantelingu, Kempegowda; Rangappa, Kanchugarakoppal S.
Abstract : Various imidazo- and triazolo-pyridines were synthesised by the intramolecular cyclization of pyridine 2-methylamine and dithioesters under mild conditions. Abstract : T3P–DMSO mediated desulfurative cyclization of in situ generated thioamides serves as an efficient and versatile method for the synthesis of imidazo[1, 5- a ]pyridines and [1, 2, 4]-triazolo[4, 3- a ]pyridines with good to excellent yields. Substrates such as 2-methylaminoquinoline and pyrazin-2-yl-methanamine also undergo the corresponding reactions at room temperature. This efficient protocol has several advantages such as mild conditions, short reaction time, operational simplicity and high yields.